Aristophanes and the cult of the saviour - Currie, B (Salvatore Sciascia Editore, 2020)
Aristophanes’ Knights, Peace, and Birds are deeply interested in the figure of the civic “saviour”, who is depicted as a Gottmensch: a man become god or, at least, a man deserving of religious treatment such as the gods receive. While the Aristophanic treatment of the theme contains many parodic, paratragic, and metatheatrical elements, it arguably still offers a utilizable and unique window onto real-life practices concerning fifth-century BCE Gottmensch- and saviour-figures. Aristophanic comedy consequently has a role to play in the reconstruction of the early history of saviour- and ruler-cult, prior to the divine cult given to Lysandros in his own lifetime at Samos in 404 BCE.